Clinical and dopamine transporter imaging characteristics of non-manifest LRRK2 and GBA mutation carriers in the Parkinson's Progression Markers Initiative (PPMI): a cross-sectional study. Issue 1 (January 2020) - Simuni, Tanya; Uribe, Liz; Cho, Hyunkeun Ryan; Caspell-Garcia, Chelsea; Coffey, Christopher S; Siderowf, Andrew; Trojanowski, John Q; Shaw, Leslie M; Seibyl, John; Singleton, Andrew; Toga, Arthur W; Galasko, Doug; et al.
Summary: Background: The Parkinson's Progression Markers Initiative (PPMI) is an ongoing observational, longitudinal cohort study of participants with Parkinson's disease, healthy controls, and carriers of the most common Parkinson's disease-related genetic mutations, which aims to define biomarkers of Parkinson's disease diagnosis and progression. All participants are assessed annually with a battery of motor and non-motor scales, 123-I Ioflupane dopamine transporter (DAT) imaging, and biological variables. We aimed to examine whether non-manifesting carriers of LRRK2 and GBA mutations have prodromal features of Parkinson's disease that correlate with reduced DAT binding. Methods: This cross-sectional analysis is based on assessments done at enrolment in the subset of non-manifesting carriers of LRRK2 and GBA mutations enrolled into the PPMI study from 33 participating sites worldwide. The primary objective was to examine baseline clinical and DAT imaging characteristics in non-manifesting carriers with GBA and LRRK2 mutations compared with healthy controls. DAT deficit was defined as less than 65% of putamen striatal binding ratio expected for the individual's age. We used t tests, χ 2 tests, and Fisher's exact tests to compare baseline demographics across groups. An inverse probability weighting method was applied to control for potential confounders such as age and sex. To account for multiple comparisons, we applied a family-wise error rate to each set of analyses. This study is registered with ClinicalTrials.gov, number NCT01141023 . Findings: Between Jan 1, 2014, and Jan 1, 2019, the study enrolled 208 LRRK2 (93% G2019S) and 184 GBA (96% N370S) non-manifesting carriers. Both groups were similar with respect to mean age, and about 60% were female. Of the 286 (73%) non-manifesting carriers that had DAT imaging results, 18 (11%) LRRK2 and four (3%) GBA non-manifesting carriers had a DAT deficit. Compared with healthy controls, both LRRK2 and GBA non-manifesting carriers had significantly increased mean scores on the Movement Disorders Society Unified Parkinson's Disease Rating Scale (total score 4·6 [SD 4·4] healthy controls vs 8·4 [7·3] LRRK2 vs 9·5 [9·2] GBA, p<0·0001 for both comparisons) and the Scale for Outcomes for PD – autonomic function (5·8 [3·7] vs 8·1 [5·9] and 8·4 [6·0], p<0·0001 for both comparisons). There was no difference in daytime sleepiness, anxiety, depression, impulsive–compulsive disorders, blood pressure, urate, and rapid eye movement (REM) behaviour disorder scores. Hyposmia was significantly more common only in LRRK2 non-manifesting carriers (69 [36%] of 194 healthy controls vs 114 [55%] of 208 LRRK2 non-manifesting carriers; p=0·0003). Finally, GBA but not LRRK2 non-manifesting carriers showed increased DAT striatal binding ratios compared with healthy controls in the caudate (healthy controls 2·98 [SD 0·63] vs GBA 3·26 [0·63]; p<0·0001), putamen (2·15 [0·56] vs 2·48 [0·52]; p<0·0001), and striatum (2·56 [0·57] vs 2·87 [0·55]; p<0·0001). Interpretation: Our data show evidence of subtle motor and non-motor signs of Parkinson's disease in non-manifesting carriers compared with healthy controls that can precede DAT deficit. Longitudinal data will be essential to confirm these findings and define the trajectory and predictors for development of Parkinson's disease. Funding: Michael J Fox Foundation for Parkinson's Research.